Closed solutions to a differential-difference equation and an associated plate solidification problem - Layeni, Olawanle P.; Akinola, Adegbola P.; Johnson, Jesse V. (SpringerPlus, 2016)
Two distinct and novel formalisms for deriving exact closed solutions of a class of variable-coefficient differential-difference equations arising from a plate solidification problem are introduced. Thereupon, exact closed traveling wave and similarity solutions to the plate solidification problem are obtained for some special cases of time-varying plate surface temperature.